Don Quixote by Alexander Gorsky after Marius Petipa, music by Léon Minkus Soslan Kulaev (Don Quixote), Viktoria Tereshkina (Kitri), Kimin Kim (Basilio)... -- Mariinsky Theater Ballet Company - Gorsky, Alexander (Telmondis, 2021)
Relive the whimsical adventures of Kitri, Basilio, and Don Quixote, live from the hallowed stage of the magnificent Mariinsky Theatre. Léon Minkus's music and the timeless choreography by Alexander Gorsky (following Marius Petipa's original) make this ballet an unending source of wonder. Soslan Kulaev shines in the title role, with the magnificent Viktoria Tereshkina and Kimin Kim as Kitri and Basilio, all surrounded by the sublime dancers of the peerless Mariinsky Ballet. The orchestra's interpretation of the score draws the audience into the veritably quixotic universe of this landmark of the ballet repertoire
Keywords: ballet; Webcast; Internet videos; Vidéos sur Internet